Autentizace v přímém bankovnictví - Hub, Miloslav (Univerzita Pardubice, 2003)
The aim of this text is to show how authentication is implemented in on-line banking industry. Czech banks are analyse as well as their on-line banking services. It is examined authentication of user's identity of this services.
Keywords: přímé bankovnictví; Autentizace; bezpečnost